Vitamin D, vitamin D supplementation and atrial fibrillation risk in the general population: updated systematic review and meta-analysis of prospective studies - Ding, Xiaoli; Lai, Jiying; Zhang, Hehui; Guo, Zongwen (Frontiers in Nutrition, 2023)
Background: Since the association of vitamin D with atrial fibrillation (AF) risk is still unclear, we conducted this updated meta-analysis of prospective studies to identify the relationship between vitamin D or vitamin D supplementation and AF in the general population. Methods: We conducted a comprehensive search of multiple databases up to May 2023 for studies reporting vitamin D and AF. The hazard ratios (HRs) with 95% confidence intervals (CIs) were pooled by a random-effects model. Results: A total of seven studies were included in this meta-analysis. Vitamin D deficiency (<20 ng/ml) was associated with increased AF incidence (HR: 1.12, 95% CI: 1.005-1.25). The HR was not significant with vitamin D insufficiency (20-30 ng/ml) (HR: 1.09, 95% CI: 0.98-1.21). Each 10 ng/ml increase in serum vitamin D was associated with a significantly decreased AF incidence (HR: 0.95, 95% CI: 0.93-0.97). Two studies reported the effect of vitamin D supplements on AF incidence but reached inconsistent results. Conclusions: Vitamin D deficiency or insufficiency was associated with an increased risk of AF in the general population. The role of vitamin D supplementation in AF prevention needs further investigation.